Rudolf Desselbruner: printer, publisher and editor – Part 2 (Libellarium: journal for research in the field of information and related sciences, 2021)
Purpose. The paper deals with the life and achievements of the printer, publisher and editor Rudolf Desselbrunner (Graz, 1851 - Gradačac, 1931) and his newspapers Galeb, Vragoljan and Kvarner published mainly in Bakar with the exception of only a couple of issues in Sušak.  Including several intervals, the publishing period covers the time span from 1878 until 1892. Due to extensive information on Desselbrunner’s publishing legacy and so far unknown particulars from his life, the paper has been divided into two parts. The second part of the paper is dedicated to the familiarisation of readers with the three newspapers he printed, published and edited mostly himself. In doing so, it was the authors’ intention to facilitate online retrieval of the selected articles so that they can be utilised for gaining new knowledge on typography, social and political events in Croatian Littoral throughout the second half of the 19th century.Methodology. In order to achieve the envisaged purpose, the authors read and analysed the articles of the three newspapers selecting 245 of them as a representative sample applying the historical-descriptive approach and the method of content analysis. Subsequently, all of them were arranged following the methodology of contents analysis.Findings. This paper has brought about three tangible results. Firstly, an insight into Desselbrunner’s available life particulars, his activities, and the contents of his articles have been obtained. In such a way easy access to the articles has been enabled thus facilitating further research for information scientists, historians, ethnologists and dialectologists. Secondly, it has been proved that Desselbrunner is to be credited with the promotion of civil liberties, freedom of press and speech as well as the setting up of dialogue culture. The third result of this paper is the proof that Rudolf Desselbrunner provided written evidence of numerous social events in Bakar and the surrounding area, thereby offering valuable additional resources for writing local history.Originality. The originality of the paper may be observed from the specific approach applied in the presentation of articles, bearing in mind the fact that a similar approach has not been encountered in writing about either major Rijeka or older Croatian newspapers.Keywords: Bakar, newspapers Galeb, newspapers Kvarner, Rudolf Desselbrunner, newspapers Vragoljan
Keywords: Bakar; newspapers Galeb; newspapers Kvarner; Rudolf Desselbrunner; newspapers Vragoljan